## Expanding (6m-2)^2

The expression (6m-2)^2 represents the square of the binomial (6m-2). To expand this, we can use the **FOIL method** or the **square of a difference** formula.

### Using the FOIL Method

FOIL stands for **First, Outer, Inner, Last**. This method helps us multiply two binomials:

**First:**Multiply the first terms of each binomial: (6m) * (6m) = 36m^2**Outer:**Multiply the outer terms of the binomials: (6m) * (-2) = -12m**Inner:**Multiply the inner terms of the binomials: (-2) * (6m) = -12m**Last:**Multiply the last terms of each binomial: (-2) * (-2) = 4

Now, combine all the terms: 36m^2 - 12m - 12m + 4

Finally, simplify by combining like terms: **36m^2 - 24m + 4**

### Using the Square of a Difference Formula

The square of a difference formula states: (a - b)^2 = a^2 - 2ab + b^2

In our case, a = 6m and b = 2. Applying the formula:

(6m - 2)^2 = (6m)^2 - 2(6m)(2) + (2)^2

Expanding and simplifying: 36m^2 - 24m + 4

Therefore, both methods lead to the same expanded form: **(6m-2)^2 = 36m^2 - 24m + 4**